2023
DOI: 10.3389/fpls.2023.1079221
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of tissue-specific non-coding RNAs in black pepper (Piper nigrum L.)

Abstract: Long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) are the two classes of non-coding RNAs (ncRNAs) present predominantly in plant cells and have various gene regulatory functions at pre- and post-transcriptional levels. Previously deemed as “junk”, these ncRNAs have now been reported to be an important player in gene expression regulation, especially in stress conditions in many plant species. Black pepper, scientifically known as Piper nigrum L., despite being one of the most economically important s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The investigation into tissue-specific circRNAs in common carp gave 22,854 circRNAs and GO analysis suggests that lncRNAs/circRNAs play a crucial role in various cellular processes, including transcriptional regulation, signaling pathways, and enzymatic reactions, which could have implications for various biological processes, including development, growth, directly involved in immunity, and disease ( Xiu et al, 2021 ). For identification of circRNAs on common carp, CIRI2 was used owing to its robustness and reliability as compared to other methods, based on numerous literature ( Gao et al, 2018 ; Chen et al, 2022 ; Kumar et al, 2023 ; Rbbani et al, 2023 ). In tilapia fish, ten and eleven circular RNAs were predicted to target miR-221 and miR-222, correspondingly.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation into tissue-specific circRNAs in common carp gave 22,854 circRNAs and GO analysis suggests that lncRNAs/circRNAs play a crucial role in various cellular processes, including transcriptional regulation, signaling pathways, and enzymatic reactions, which could have implications for various biological processes, including development, growth, directly involved in immunity, and disease ( Xiu et al, 2021 ). For identification of circRNAs on common carp, CIRI2 was used owing to its robustness and reliability as compared to other methods, based on numerous literature ( Gao et al, 2018 ; Chen et al, 2022 ; Kumar et al, 2023 ; Rbbani et al, 2023 ). In tilapia fish, ten and eleven circular RNAs were predicted to target miR-221 and miR-222, correspondingly.…”
Section: Discussionmentioning
confidence: 99%
“…chinensis), it was observed that lncRNAs and miRNAs regulate heat stress responses through pathways associated with plant hormones ( Wang et al, 2019 ). Using publicly available RNA-seq data, exploring lncRNAs and their regulatory networks in plants has become a feasible strategy ( Chen, Zhong & Qi, 2021 ; Kumar et al, 2023 ; Xie et al, 2023a ; Xie et al, 2023b ). For instance, under drought stress conditions, Chen et al (2021) identified a set of upregulated lncRNAs involved in regulating genes related to carbon fixation, chlorine metabolism, and fatty acid synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNAs were distributed unevenly across the 11 opium poppy chromosomes, consistent with previous ndings (Guo et al 2018; Hong et al 2022).It is well known that lncRNAs show tissue-or developmental stage-speci c expression pro les(Budak et al 2020). Previous studies have shown that tissue-speci cally expressed lncRNAs often have speci c functions(Zhao et al 2020;Kumar et al 2023…”
mentioning
confidence: 99%